I sistemi di gestione delle acque a Nora (Sardegna) in età punica e romana: le opere di canalizzazione (ACME, 2020)
The systems for conveying, distributing and discharging water in ancient cities were of a focal and indispensable importance, because without their proper functioning it would not have been possible to overcome even the necessary daily activities related to the use of water. They therefore assumed a precise planning in the construction of water management systems, as well as in the control and maintenance of them. In this regard, the city of Nora in Sardinia presented a wide range of exemplars, analyzed both in the technical-constructive aspects and in relation to the historical-urban evolution of the site: from private and public distribution and drainage networks, built with waterproofed stone materials, in opus caementicium, in specific ceramic tubules or bricks, or with a series of amphorae inserted one into the other, to some examples of lead fistulae, to the aqueduct that conveyed the water towards the city and to the underground sewers.